Perspective on Protein Arginine Deiminase Activity—Bicarbonate Is a pH-Independent Regulator of Citrullination - Zhou, Yebin; Mittereder, Nanette; Sims, Gary P. (Frontiers in Immunology, 2018)
Protein citrullination catalyzed by protein arginine deiminases (PADs) is involved in autoimmune disease pathogenesis, especially in rheumatoid arthritis. Calcium is a key regulator of PAD activity, but under normal physiological conditions it remains uncertain how intracellular calcium levels can be raised to sufficiently high levels to activate these enzymes. In pursuit of trying to identify other factors that influence PAD activity, we identified bicarbonate as a critical regulator of PAD activity. We demonstrate that physiological levels of bicarbonate upregulate citrullination by recombinant PAD2/4 and endogenous PADs in neutrophils. The impact of bicarbonate is independent of calcium and pH. Adding bicarbonate to commercial PAD activity kits could increase assay performance and biological relevance. These results suggest that citrullination activity is regulated by multiple factors including calcium and bicarbonate. We also provide commentary on the current understanding of PAD regulation and future perspective of research in this area.